Arabic Language Learning in Cybernetic Theory Perspective: A Case Study of Hayfa Academy as an Effort to Improve SDGs4 - Keysha Shira Zafirah; Syihabuddin; Shofa Mustafa Khalid; Mia Nurmala (Postgraduate of IAIN Metro Lampung Indonesia, 2025)
The quality of Arabic speaking skills among students tends to be low. This quality hurts their effective communication skills. This problem needs to be addressed because it hinders the achievement of the Sustainable Development Goals (SDGs). Arabic is essential for establishing effective communication in the global world. This study explores in depth the Arabic language learning process of Hayfa Academy from the perspective of cybernetic theory and its contribution to the achievement of SDG 4. With a qualitative method and case study approach, this study collected data through interviews, distributing questionnaires, and observations. Data that has been obtained is then analyzed using collecting data, direct interpretation, forming patterns, and naturalistic generalization as a conclusion. The results of this study reveal that Hayfa Academy uses cybernetic theory in its learning process, namely giving attention to internal and external conditions of students. Hayfa Academy's Arabic language learning process also has a positive impact on the achievement of SDG 4. Hayfa Academy has implemented the Arabic language learning process by paying attention to the achievement of SDG 4, especially point 4, namely student skills and quality education.